Risk factors associated with burnout among Medical Faculty: a systematic review - Alvandi, Maryam; Davis, Jenna (Nursing in the 21st Century, 2023)
RISK FACTORS ASSOCIATED WITH BURNOUT AMONG MEDICAL FACULTY: A SYSTEMATIC REVIEWAim. Burnout syndrome in academicians of healthcare professions adversely aff ects their well-being and performance during work, and it is considered common worldwide. The aim of this systematic review was to identify burnout factors among medical faculty.Material and methods. Electronic searches were conducted in Citations and Abstracts for Literature of Nursing and Allied Health (CINAHL) Plus with full text, MEDLINE with full text, Academic Search Complete, and PsycInfo following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. After excluding duplicates and articles, which did not meet the inclusion criteria, 17 studies were included in the final analysis. The Quality Index checklist developed by Downs & Black was used to evaluate the methodological quality of the included studies. There are no randomized controlled trials in our area of interest, and non-randomized studies scored low.Results. A total of 17 studies (7,056 participants) across six countries were compatible with the inclusion criteria. Main associated factors of burnout included socio-demographic and work-related characteristics; physician factors (age, gender minority status, disability, desire to reduce the workload) and workplace culture; demographic factors, including sex, ethnicity/race, years of experience, specialty, and work-related factors; lack of institutional factors, such as mentorship, collaboration opportunities, feelings of empowerment, value, and support of well-being; poor faculty relationships and professional behaviors; perceived stressors, spousal/partner support, self-efficacy, and depression; long working hours, interpersonal interactions among the colleagues, family and social factors, including challenges related specifically to women, feelings and emotions, and personal qualities; high workload, limited time off, nature of work (high stake job), stigma/culture around burnout, administrative burden, lack of autonomy, and frequent performance feedback; high schedule misalignment; inadequate professional fulfillment, culture of wellness, personal reliance, and efficiency of practice; lack of organizational justice and job satisfaction; and anxiety-depression levels.Conclusions. There was a considerable prevalence of burnout among medical faculty, which can be debilitating. Burnout among medical faculty remains the greatest threat to institutional growth and success.